1885 Ill. Rev. Stat. 771 - (:unkn) unknown (My University, 1885)
Criminal Code Ch. 38, para. 90: Required all dealers to keep a registration of all deadly weapons sold or given away, including any slung-shot, metallic knuckles, pistol, revolver, derringer, Bowie knife, dirk, or other deadly weapon.
Keywords: REGISTRATION